Manuscript Diversity, Meaning, and Variance in Juan Manuel's El Conde Lucanor - De Looze, Laurence Neil, 1953- (Book collections on Project MUSE., 2006)
De Looze's complex and nuanced reading sheds new light on an important work and makes a significant contribution to medieval studies, Spanish studies, and the history of the book.